Effects of chemical reaction on transient MHD flow with mass transfer past an impulsively fixed infinite vertical plate in the presence of thermal radiation - Reddy, B. Prabhakar (Zielona Góra: Uniwersytet Zielonogórski)
The effects of chemical reaction on a transient MHD mixed convection flow with mass transfer past an impulsively fixed infinite vertical plate under the influence of a transverse magnetic field have been presented. The medium is considered to be non-scattering and the fluid to be non-gray having emitting-absorbing and optically thick radiation limit properties. The dimensionless governing equations of the flow and mass transfer with boundary conditions are solved numerically by using the Ritz finite element method.
Keywords: MHD; magnetic field; fixed vertical plate; chemical reaction parameter; radiation parameter